Linear 2′ O-Methyl RNA probes for the visualization of RNA in living cells - Molenaar, C. (Oxford University Press, 2001)
U1snRNA, U3snRNA, 28 S ribosomal RNA, poly(A) RNA and a specific messenger RNA were visualized in living cells with microinjected fluorochrome-labeled 2′ O-Methyl oligoribonucleotides (2′ OMe RNA). Antisense 2′ OMe RNA probes showed fast hybridization kinetics, whereas conventional oligodeoxyribonucleotide (DNA) probes did not. The nuclear distributions of the signals in living cells were similar to those found in fixed cells, indicating specific hybridization. Cytoplasmic ribosomal RNA, poly(A) RNA and mRNA could hardly be visualized, mainly due to a rapid entrapment of the injected probes in the nucleus. The performance of linear probes was compared with that of molecular beacons, which due to their structure should theoretically fluoresce only upon hybridization. No improvements were achieved however with the molecular beacons used in this study, suggesting opening of the beacons by mechanisms other than hybridization. The results show that linear 2′ OMe RNA probes are well suited for RNA detection in living cells, and that these probes can be applied for dynamic studies of highly abundant nuclear RNA. Furthermore, it proved feasible to combine RNA detection with that of green fluorescent protein-labeled proteins in living cells. This was applied to show co-localization of RNA with proteins and should enable RNA–protein interaction studies.